Federico García Lorca y el cine - Roberts, Stephen G.H. (Centre National du Livre, 2015)
This article analyses Federico García Lorca's relationship with cinema, taking into account not only his screenplays but also his incorporation into his drama and poetic works of techniques borrowed from cinema.